Effect of plant growth regulators on plant regeneration of hyacinth bean (Lablab purpureus (L.) Sweet) through nodal explants - Islam, MT; Haque, MS; Rahman, S; Molla, MR; Keller, ERJ (Bangladesh Journal of Agricultural Research, 2019)
Nodal explants of three accessions namely BD-101, BD-122 and BD-8001 of hyacinth bean (Lablab purpureus (L.) Sweet) were cultured for four weeks on MS medium supplemented with different concentrations and combinations of NAA (0, 0.1 mgl-1) and BAP (0.5, 1.0 and 2.5 mgl-1) for plant regeneration. The highest shoot initiation was observed in 0.5 mgl-1 BAP while the lowest shoot initiation was found in 2.5 mgl-1 BAP with 0.1 mgl-1 NAA. Earlier shoot initiation was exhibited in 0.5 mgl-1 BAP with 0.1 mgl-1 NAA. The highest number of leaflets and higher shoot lengths were observed in MS medium. Comparatively higher number of shoots was found in BAP (0.5-2.5 mgl-1). The highest percentage of callus was initiated in medium supplemented with 1.0 mgl-1 BAP. Earlier callus initiation and larger callus size were found in combination of BAP (0.5-2.5 mgl-1) with 0.1 mgl-1 NAA. BD-122 cultured in MS medium was found superior for shoot regeneration through node culture. Four different concentrations of IBA (0.1-1.5 mgl-1) were used for rooting. The highest percentage (86.67 %) of rooting was found in MS medium containing 0.1 mgl-1 IBA at four weeks. Rooting frequency decreased with the increasing concentration of IBA. The accession BD-8001 had 99.60 % rooting in 0.5 mgl-1 IBA. The highest number of longest roots was exhibited in 0.1 mgl-1 IBA. The regeneration protocol developed from nodal explants has applicability in improvement of hyacinth bean. Bangladesh J. Agril. Res. 44(1): 27-42, March 2019